Helicobacter pylori-derived heat shock protein 60 increases the induction of regulatory T-cells associated with persistent infection. (June 2018) - Hsu, Wei-Tung; Ho, Shu-Yi; Jian, Ting-Yan; Huang, Han-Ning; Lin, Yu-Ling; Chen, Chia-Hung; Lin, Tsung-Han; Wu, Ming-Shiang; Wu, Chang-Jer; Chan, Yi-Lin; Liao, Kuang-Wen
Abstract: Local Treg responses are involved in Helicobacter pylori -related inflammation and clinical outcomes after infection, and H. pylori -derived HSP60 (HpHSP60) is an important virulence factor associated with gastric carcinogenesis. This study to investigate the role of HpHSP60 in immunosuppression, particularly with regard to whether it could induce the production of Treg cells. For this purpose, human peripheral blood mononuclear cells (PBMCs) were treated with or without HpHSP60 in the presence of an anti-CD3 mAb to determine the effect of HpHSP60 on cell proliferation. In this report, HpHSP60 decreased the expression of CDK4 to significantly arrest the proliferation of mitogen-stimulated T-cells, which correlated with the induction of Treg cells. Moreover, monocytic cells were essential for the induction of HpHSP60-induced Treg cells via the secretion of IL-10 and TGF-β after treatment with HpHSP60. Blockage of HpHSP60 with specific monoclonal antibodies significantly reduced the colonization of H. pylori and the expression of Treg cells in vivo . Overall, our results suggest that HpHSP60 could act on macrophages to trigger the expression of IL-10 and TGF-β, thereby leading to an increase in Treg cells and inhibition of T-cell proliferation. Graphical abstract: Highlights: H. pylori -derived HSP60 mediates host monocytes to increase the numbers and activities of Treg cells. H. pylori -derived HSP60 can stimulate the expression of IL-8 and TGF-β in host monocytes. Blocking of H. pylori -derived HSP60 could attenuate the infection of H. pylori in vivo.